Thoracic ectopia cordis: A case report - Danang Himawan Limanto; Heroe Soebroto (Faculty of Medicine, Universitas Islam Indonesia, 2020)
Ectopia Cordis is a congenital anomaly in which the heart is located abnormally outside the thoracic cavity. Aetiology of this defect is still unclear with the incidence rate of 8:1,000,000 live births. Clinical manifestations usually present as severe sepsis respiratory distress due to heart failure as a result of an intrinsic abnormality of the heart which makes the management more challenging. Five days-old female newborn was referred to our hospital by a local doctor with “beating lump” outside her chest. The diagnosis of complete thoracic ectopia cordis was made by clinical examination, chest x-ray, and echocardiography. The Echo showed complete AV canal, ASD, mild pulmonary stenosis, and atrioventricular valve regurgitation. Palliative surgery was then undertaken with the initial goal to limit exposure and prevent further infection. The heart is covered with bovine pericardium sutured along the edge of the chest wall defect. Ectopia cordis is rare and has a poor prognosis especially thoracic and cervical types. Definitive surgery, to replace the heart to the thoracic cavity, is difficult to perform because of the hypoplastic thoracic cavity. Attempt to do palliative surgery, such as covering the heart with either skin flap or other material, becomes the choice of treatment in this case although there is no evidence reported of adulthood survivors.